2022
DOI: 10.3389/fphar.2022.819826
|View full text |Cite
|
Sign up to set email alerts
|

Ilex rotunda Thunb Protects Against Dextran Sulfate Sodium-Induced Ulcerative Colitis in Mice by Restoring the Intestinal Mucosal Barrier and Modulating the Oncostatin M/Oncostatin M Receptor Pathway

Abstract: Ilex rotunda Thunb (IR) is a traditional Chinese medicine used for the clinical treatment of gastric ulcers and duodenal ulcers; however, the effect of IR on ulcerative colitis (UC) and its underlying mechanism remains unclear. This study investigated the therapeutic effect of IR on UC mice induced by dextran sulfate sodium (DSS) as well as the potential underlying mechanism. The main components of IR were analyzed by ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry. Then we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…DSS is known to elevate intestinal mucosal permeability, upregulate specific inflammatory factors, and disrupt the balance of intestinal microbiota, triggering inflammation [ 46 ]. Numerous pro- and anti-inflammatory cytokines are important participants in intestinal inflammation [ 47 ]. TNF-α, IL-1β, and IL-6 work together to stimulate the production of adhesion molecules, chemokines, and other cytokines, which in turn promotes inflammation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…DSS is known to elevate intestinal mucosal permeability, upregulate specific inflammatory factors, and disrupt the balance of intestinal microbiota, triggering inflammation [ 46 ]. Numerous pro- and anti-inflammatory cytokines are important participants in intestinal inflammation [ 47 ]. TNF-α, IL-1β, and IL-6 work together to stimulate the production of adhesion molecules, chemokines, and other cytokines, which in turn promotes inflammation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In instances of UC, augmented apoptotic cell and histiocyte counts within the lamina propria are observed, the latter facilitating phagocytosis of apoptotic cells [ 32 ]. Scholarly discourse highlights the pivotal role of intestinal epithelial cell demise in perpetuating colitis-associated inflammation and compromised barrier integrity [ 33 , 34 ]. The confluence of increased intestinal epithelial cell mortality and heightened inflammatory cell presence precipitates the enduring course of UC.…”
Section: Discussionmentioning
confidence: 99%
“…During UC, the lamina propria has more apoptotic cells and histiocytes, the latter of which is used to phagocytose apoptotic cells [31]. Studies have shown that the death of intestinal epithelial cells is responsible for the persistence of in ammation in colitis and impaired barrier function [32,33]. The death of intestinal epithelial cells and the increase of in ammatory cells lead to long-lasting UC.…”
Section: Discussionmentioning
confidence: 99%